2013
DOI: 10.1021/jp4046512
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Thermal Conduction Characteristics of Phase Change Composites with Single-Walled Carbon Nanotube Inclusions

Abstract: We report strikingly large contrasts in the thermal conductivity enhancement of phase change alkane in liquid and solid state with single-walled carbon nanotube (SWCNT) inclusions. With a small SWCNT loading of 0.25 wt % a strikingly high, 250% enhancement is achieved in the solid state and a nominal enhancement of 10% is achieved in the liquid state. The thermal conductivity contrast between solid and liquid state was found to increase with increasing SWCNT loading. The thermal conductivity contrast was more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…For such nanocomposites, they reported that the electrical and thermal conductivity contrast ratio (solid state conductivity to the liquid state conductivity) can vary by a factor of 5 and 2 respectively. Harish et al [17] reported that for n-octadecane/single walled carbon nanotube nanocomposite the thermal conductivity enhancement in liquid state is nominal and in good agreement with the predictions of classical theoretical models, while in solid state, the thermal conductivity enhancement is anomalous and beyond the predictions of classical theories. Recently, Angayarkanni and Philip [18] reported that the thermal conductivity of n-hexadecane can be significantly enhanced using inexpensive cationic and anionic surfactants.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…For such nanocomposites, they reported that the electrical and thermal conductivity contrast ratio (solid state conductivity to the liquid state conductivity) can vary by a factor of 5 and 2 respectively. Harish et al [17] reported that for n-octadecane/single walled carbon nanotube nanocomposite the thermal conductivity enhancement in liquid state is nominal and in good agreement with the predictions of classical theoretical models, while in solid state, the thermal conductivity enhancement is anomalous and beyond the predictions of classical theories. Recently, Angayarkanni and Philip [18] reported that the thermal conductivity of n-hexadecane can be significantly enhanced using inexpensive cationic and anionic surfactants.…”
Section: Introductionmentioning
confidence: 65%
“…Schiffres et al [16] showed that the aspect ratio of such needle like structures can vary from micromillimeter scale depending on the cooling rate in phase change alkanes. Hence, it is possible that during solidification process, SWCNH nano inclusions tend to get entrapped within the crystalline boundaries thereby creating "nano-rich" inter-crystalline region [15][16][17]. Zheng et al [15] suggested that the anisotropic growth of needle like structures generates stress and increase the contact area of the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…When lauric acid undergoes phase change from liquid to solid state, it forms needle-like crystalline structures whose aspect ratio can vary from micro-millimeter scales depending on the freezing speed [33]. During the crystallization process, it is possible that the MLG nanoplatelets are entrapped within the grain boundaries of the crystalline structures thereby creating "nano rich" inter-crystalline region [18,34]. We hypothesize that these inter-crystalline region provide additional heat transport pathways resulting in the enhanced thermal conductivity of the nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the thermal conductivities of the solid CPCMs increase greater than those of the liquid CPCMs.It is known that the thermal conductivity of the CPCMs in the solid state is higher than that of the CPCMs in the liquid state due to its crystalline nature. The mechanisms of the thermal conductivity enhancement in solid state and liquid state have been clearly explained by Schiffres et al[39], Harish et al[40] and Angayarkanni et al[41]. The higher thermal conductivity enhancement of the CPCMs in the solid state is possibly due to the formation of continuous networking structure during the phase transition process.…”
mentioning
confidence: 89%
“…When the crystals begin to nucleate forming needle-like structures during solidifying, the CNTs are gradually pushed to the grain boundaries, thereby leading to form a continuous quasi-2D network of bundles which in turn recovers its original form when melted back. There is no significant thermal conductivity improvement of the CPCMs in the liquid state due to the absence of such continuous structures as the heat conduction is heavily limited by high interface resistance between the CNTs and the surrounding fluid and contact resistance between the CNTs[40].…”
mentioning
confidence: 99%